Beyond the Signal: Communal Tethering as a Framework for Authentic Communication in Archipelagic Asynchronicity - Gerum Quiming (Future Science / FSH-PH Publications, 2026)
The Philippine educational landscape in 2026 continues to reflect a persistent tension between the demand for real-time synchronous learning and the structural realities of intermittent internet connectivity across an archipelagic nation. This conceptual review develops Communal Tethering as a culturally grounded framework for understanding authentic communication in contexts characterized by what this study terms Archipelagic Asynchronicity. Using a narrative synthesis approach guided by Popay et al. (2006), the study examined 42 peer-reviewed articles and policy documents published between 2020 and 2026, sourced from Scopus, ERIC, Google Scholar, and official repositories of UNESCO, the Department of Education (DepEd), and the Commission on Higher Education (CHED). Through thematic mapping, the analysis identifies recurring patterns in which intermittent connectivity, rather than functioning solely as a limitation, creates opportunities for reflective engagement and localized meaning-making. These conditions are sustained through what this study conceptualizes as Digital Bayanihan Dynamics, wherein culturally embedded practices of mutual support enable continuity in learning despite technological fragmentation. The paper contends that authentic communication in resource-constrained environments depends less on constant connectivity and more on relational permanence. By shifting the focus from speed-centered models to culturally grounded relational frameworks, this study offers both theoretical and practical contributions to English Language Teaching and mediated communication in Global South contexts.